2010
DOI: 10.1111/j.1600-0838.2010.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Injury incidence in hip hop dance

Abstract: Hip hop dance has rapidly become a popular international art form. There is limited information on injury patterns in this population. The purpose of this study was to determine injury incidence and patterns among three groups of hip hop dancers. Three hundred and twelve intermediate, advanced, and expert hip hop dancers were recruited at battles, dance conferences, clubs, and on dance related web sites within the United States and internationally. A Web-based survey was conducted over a 6-month period. Inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
4
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 28 publications
7
69
4
4
Order By: Relevance
“…This is followed in level of attention in the literature, perhaps surprisingly, by break dance121 (usually referred to as breaking by its participants, who are called “b-boys” and “b-girls”), and modern/contemporary dance 22–40. Other dance genres that have received research consideration, though comparatively not as much, include hip-hop,41 flamenco,4244 ballroom,45–51 Highland,52,53 and Irish 5460. Investigation of some of these is becoming more frequent.…”
Section: The Nature Of Dance Injury and Dance Injury Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…This is followed in level of attention in the literature, perhaps surprisingly, by break dance121 (usually referred to as breaking by its participants, who are called “b-boys” and “b-girls”), and modern/contemporary dance 22–40. Other dance genres that have received research consideration, though comparatively not as much, include hip-hop,41 flamenco,4244 ballroom,45–51 Highland,52,53 and Irish 5460. Investigation of some of these is becoming more frequent.…”
Section: The Nature Of Dance Injury and Dance Injury Researchmentioning
confidence: 99%
“…While ideal data may not be available, dance is undoubtedly associated with numerous injuries 23,24,39,41,60,6284. In research reporting the percentage of dancers injured out of a studied sample, the range was 42%–97% across a variety of genres and skill proficiencies 63,64,66,68,69,71,73,8588.…”
Section: The Nature Of Dance Injury and Dance Injury Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the inclusion and exclusion criteria (Figure 1), two authors appraised the relevance of each identified study in order to agree the final list of included studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Istraživanjem učestalosti ozljeda u skupini od 312 plesača srednjeg, naprednog i ekspertnog stupnja, čak 232 plesača prijavila su ukupno 738 ozljeda, od čega je 52 % bilo ozljeda donjih i 32 % gornjih ekstremiteta. Hip hop plesači prijavljuju stope ozljeda koje su više od ozljeda u ostalim plesnim stilovima, a usporedive su s ozljedama u gimnastici, što upućuje na važnost njihove edukacije o prevenciji ozljeda, biomehanici plesnih pokreta i potrebi korištenja zaštitne opreme (20).…”
unclassified